Diboron-carbene complexes derived from a geminal dianion - Fan, Jun (2022)
The reaction of the bis(thiophosphinoyl) geminal dianion [C(PPh2S)2]2- with B2Br4(SMe2)2 in toluene afforded the diboron-carbene complex [(SPh2P)2CB]2 (2). The lability of the boron-carbene bond was found in the reaction of the sterically hindered thiophosphinoyl iminophosphoranyl geminal dianion [C(PPh2NAr)(PPh2S)]2- (Ar = 2,6-iPr2C6H3) with B2Br4(SMe2)2 in toluene to form the diboron-carbene complex 4, where one boron center bonds with two methanediides, leading to an allyl anionic-like C═B←C2- electronic structure, while another boron center is stabilized by two imino substituents. Complex 4 underwent rearrangement via a 1,2-methanediide shift in toluene at 60 °C to give the diboron-carbene complex [(SPh2P)(ArNPh2P)CB]2 (5).